2009
DOI: 10.1177/0961203309345777
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the DNA repair gene XRCC1 and associations with systemic lupus erythematosus risk in the Taiwanese Han Chinese population

Abstract: XRCC1 plays a central role in mammalian DNA repair processes. Two polymorphisms of XRCC1, rs1799782 (Arg > Trp at codon 194) and rs25487 (Arg > Gln at codon 399), are common in the Han Chinese population. Our objective was to analyze the relationship between these two functional single-nucleotide polymorphisms (SNPs) and systemic lupus erythematosus (SLE) in the Taiwanese Han Chinese population. Genotyping was performed by polymerase chain reaction restriction fragment length polymorphism (PCR-RFLP) on 172 SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Recent studies conducted by Lin et al (2009) in the Taiwanese Han Chinese population demonstrated a statistically significant higher frequency of the XRCC1 399 Arg/Gln heterozygote in patients with SLE than in controls. In contrast, Bassi et al (2008) did not confirm the contribution of the XRCC1 Arg399Gln polymorphism to SLE development in Brazilian populations.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent studies conducted by Lin et al (2009) in the Taiwanese Han Chinese population demonstrated a statistically significant higher frequency of the XRCC1 399 Arg/Gln heterozygote in patients with SLE than in controls. In contrast, Bassi et al (2008) did not confirm the contribution of the XRCC1 Arg399Gln polymorphism to SLE development in Brazilian populations.…”
Section: Discussionmentioning
confidence: 94%
“…The meta-analysis of three independent datasets (Bassi et al, 2008;Lin et al, 2009, and present study) was conducted using the Mantel-Haenszel fixed-effect model. The effect of allele contrast (Gln vs. Arg) and the contrast for the dominant (GlnGln/GlnArg vs. ArgArg) and recessive (GlnGln vs.…”
Section: Meta-analysismentioning
confidence: 99%
“…DNA repair genes can contribute to SLE predisposition (Herrick et al, 1995), and polymorphisms of XRCC1, XRCC3, and XRCC4 genes are associated with manifestation of SLE Lin et al, 2009;Warchol et al, 2012;Salimi et al, 2014). Moreover, there are numerous variants in XRCC5, XRCC6, and XRCC7 genes, which have been associated with different diseases, such as gastric cancer (Lim et al, 2002), head and neck cancer (Chang et al, 2006), breast cancer (Fu et al, 2003), glioma (Wang et al, 2004), and AML (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
“…In the first investigation, Bassi et al could not show the association of XRCC1 polymorphism (rs25487) between SLE and healthy Brazilian individuals (10). Other investigations by Lin et al and Warchol et al showed that Arg/Arg genotype of rs25487 had a protective role against SLE in Chinese and Polish populations (8,11). In the Iranian population, only one investigation was done, in which Salimi et al showed that Arg/Gln had a protective role against SLE (6).…”
mentioning
confidence: 99%
“…In the Iranian population, only one investigation was done, in which Salimi et al showed that Arg/Gln had a protective role against SLE (6). Another SNP (rs1799782) was explored in 2 studies, which showed no association between the related SNP and SLE susceptibility (6,11). The effect of rs25489 on SLE has not been investigated and the result of another SNP, which has been investigated should be elucidated.…”
mentioning
confidence: 99%